2010
DOI: 10.1029/2009jd012913
|View full text |Cite
|
Sign up to set email alerts
|

Carbon balance of a primary tropical seasonal rain forest

Abstract: [1] The role of primary tropical rain forests in the global carbon cycle is under active debate. By combining long-term forest inventory data with physiological measurement data in a 1 ha permanent ecological research plot beneath an eddy covariance flux tower in a primary tropical seasonal rain forest, the ecosystem carbon balance was investigated and a detailed site-specific carbon budget was established. The studied ecosystem was a carbon sink as determined by both eddy covariance (1.19 Mg C ha −1 yr −1 ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 158 publications
(151 reference statements)
3
47
1
1
Order By: Relevance
“…Also, the reduction in the amount of NPP produced due to a drought estimated by this study, i.e., 4.3 -9.1 Mg ha -1 yr -1 of unavailable NPP (Table 4), are comparable to values reported by other studies (e.g., Tan et al 2010). In fact for a seasonal dry tropical forest in China, Tan et al (2010) reported a 38% reduction in NPP (i.e., 4.5 Mg biomass carbon ha -1 yr -1 lost) due to a drought.…”
Section: Heuristic Analysis Of Tropical Forest Npp and Vulnerability supporting
confidence: 79%
See 1 more Smart Citation
“…Also, the reduction in the amount of NPP produced due to a drought estimated by this study, i.e., 4.3 -9.1 Mg ha -1 yr -1 of unavailable NPP (Table 4), are comparable to values reported by other studies (e.g., Tan et al 2010). In fact for a seasonal dry tropical forest in China, Tan et al (2010) reported a 38% reduction in NPP (i.e., 4.5 Mg biomass carbon ha -1 yr -1 lost) due to a drought.…”
Section: Heuristic Analysis Of Tropical Forest Npp and Vulnerability supporting
confidence: 79%
“…In fact for a seasonal dry tropical forest in China, Tan et al (2010) reported a 38% reduction in NPP (i.e., 4.5 Mg biomass carbon ha -1 yr -1 lost) due to a drought. Fisher et al (2007) reported a similar reduction in gross primary production when they experimentally tested the response of an Amazonian rain forest to induced drought stress using a throughfall exclusion experiment.…”
Section: Heuristic Analysis Of Tropical Forest Npp and Vulnerability mentioning
confidence: 99%
“…About 46 % of annual NPP feeds the detritus cycle, and this is similar to natural forests if tree mortality is not considered (e.g., Tan et al, 2011), giving ample potential for the soil of the fruit tree ecosystem to act as a net carbon sink. The amount of NPP that increases the standing biomass, contributing to ecosystem C storage function (5 % of total NPP), is conversely much lower than in forests.…”
Section: Annual and Seasonal C Allocation Patternmentioning
confidence: 95%
“…The climate is dominated by the Indian monsoon cycle. The mean annual air temperature is 21.8 °C, and the total annual rainfall is 1493 mm, approximately 87% of which occurs during the rainy season (May to October - Tan et al 2010).…”
Section: Introductionmentioning
confidence: 99%